Third Derivative Spectrophotometric Method for Simultaneous Determination of Copper and Nickel Using 6-(2-Naphthyl)-2, 3-dihydro-1,2,4- triazine-3-thione - Maliheh Barazandeh Tehrani; Effat Souri (E-Journal of Chemistry)
A simple and sensitive derivative spectrophotometric method for simultaneous determination of nickel and copper using 6-(2- naphthyl)-2,3-dihydro-1,2,4-triazine-3-thione (NDTT) as a selective analytical reagent was developed. The complexes of metal ions with NDTT were formed immediately in basic media and extracted with chloroform. The zero-crossing measurement technique was found suitable for the direct measurement of the third-derivative value of Ni-NDTT and Cu-NDTT at 501 and 472 nm respectively. Beer’s law is obeyed in the concentration range 1-30 μg/mL for both cations with different ratios. The limit of detection was 0.26 μg/mL and 0.13 μg/mL for copper and nickel respectively. The within day and between day variations showed coefficient of variation (CV%) values less than 2.80 and 2.97 for copper and nickel respectively. The error of the determination method did not exceed 6.50%. Analysis of alloy sample showed that this method can be successfully used for simultaneous determination of Cu and Ni in real samples.